Community referral in home management of malaria in western Uganda: A case series study - Nsungwa-Sabiiti Jesca; Tomson Göran; Källander Karin; Senyonjo Yahaya; Pariyo George; Peterson Stefan (BMC, 2006)
Abstract Background Home Based Management of fever (HBM) was introduced as a national policy in Uganda to increase access to prompt presumptive treatment of malaria. Pre-packed Chloroquine/Fansidar combination is distributed free of charge to febrile children <5 years. Persisting fever or danger signs are referred to the health centre. We assessed overall referral rate, causes of referral, referral completion and reasons for non-completion under the HBM strategy. Methods A case-series study was performed during 20 weeks in a West-Ugandan sub-county with an under-five population of 3,600. Community drug distributors (DDs) were visited fortnightly and recording forms collected. Referred children were located and primary caretaker interviewed in the household. Referral health facility records were studied for those stating having completed referral. Results Overall referral rate was 8% (117/1454). Fever was the main reason for mothers to seek DD care and for DDs to refer. Twenty-six of the 28 (93%) "urgent referrals" accessed referral care but 8 (31%) delayed >24 hours. Waiting for antimalarial drugs to finish caused most delays. Of 32 possible pneumonias only 16 (50%) were urgently referred; most delayed ≥ 2 days before accessing referral care. Conclusion The HBM has high referral compliance and extends primary health care to the communities by maintaining linkages with formal health services. Referral non-completion was not a major issue but failure to recognise pneumonia symptoms and delays in referral care access for respiratory illnesses may pose hazards for children with acute respiratory infections. Extending HBM to also include pneumonia may increase prompt and effective care of the sick child in sub-Saharan Africa.